Eksplorasi Faktor-Faktor Pengaruh Keputusan Pembelian Di Aplikasi Tiktok: Celebrity Marketing, Live Streaming, Dan Viral Marketing - Sudiarto, Dimas Arfi; Ambarwati, Rita (Universitas Hamzanwadi, 2024)
What is currently stirring up the public is the TikTok application with a high level of existence compared to other applications, because TikTok provides various features that are very superior and diverse compared to other applications, this is what attracts someone to use the TikTok application. The purpose of this study was to determine the effect of celebrity marketing affiliates, live streaming and viral marketing on consumer purchasing decisions on TikTok, this study used quantitative methods, namely through distributing questionnaires with answers from 100 respondents, with a random sampling technique. Furthermore, this study applies the Smartpls application data processing media with validity tests, reliability tests and T tests as hypothesis testing to determine the results to be measured. The results obtained from measuring the relationship of variable x to y, show that all celebrity marketing affiliate, live streaming and viral marketing variables have positive results or a significant effect on purchasing decisions. The implications of this research on business people continue to strive to implement innovations or up to date ideas in marketing strategies to improve consumer behavior in deciding to purchase a product.